Soybean-meal as protein source in the diet of fingerling Labeo rohita (Hamilton) - Devi, B Chamundeswari; Vijyaraghawan, Shantha; Srinivasulu, C (The Indian Journal of Animal Sciences, 2012)
Soybean-meal was included in the lest diets of fingerling Labeo rohita at 20m, 40 and 60% level partially replacing one ofthe protein sources used in the control diet. Feed was given @ 3% of the body weight. At the end of 6 months study, growthparameters like mean body weight, FCR, VSI and HSI were estimated. Though all the test diets resulted in better performancethan control, the highest growth performance was observed at 20% inclusion of soybean-meal.